Optimization and management in manufacturing engineering : resource collaborative optimization and management through the Internet of Things /: resource collaborative optimization and management through the Internet of Things. (2017) - Liu, Xinbao; Pei, Jun; Liu, Lin; Cheng, Hao; Zhou, Mi; Pardalos, P. M (Panos M.), 1954-
No abstract available